3y+14+(2y-7)=7y+(9-4y)

Simple and best practice solution for 3y+14+(2y-7)=7y+(9-4y) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3y+14+(2y-7)=7y+(9-4y) equation:


Simplifying
3y + 14 + (2y + -7) = 7y + (9 + -4y)

Reorder the terms:
3y + 14 + (-7 + 2y) = 7y + (9 + -4y)

Remove parenthesis around (-7 + 2y)
3y + 14 + -7 + 2y = 7y + (9 + -4y)

Reorder the terms:
14 + -7 + 3y + 2y = 7y + (9 + -4y)

Combine like terms: 14 + -7 = 7
7 + 3y + 2y = 7y + (9 + -4y)

Combine like terms: 3y + 2y = 5y
7 + 5y = 7y + (9 + -4y)

Remove parenthesis around (9 + -4y)
7 + 5y = 7y + 9 + -4y

Reorder the terms:
7 + 5y = 9 + 7y + -4y

Combine like terms: 7y + -4y = 3y
7 + 5y = 9 + 3y

Solving
7 + 5y = 9 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
7 + 5y + -3y = 9 + 3y + -3y

Combine like terms: 5y + -3y = 2y
7 + 2y = 9 + 3y + -3y

Combine like terms: 3y + -3y = 0
7 + 2y = 9 + 0
7 + 2y = 9

Add '-7' to each side of the equation.
7 + -7 + 2y = 9 + -7

Combine like terms: 7 + -7 = 0
0 + 2y = 9 + -7
2y = 9 + -7

Combine like terms: 9 + -7 = 2
2y = 2

Divide each side by '2'.
y = 1

Simplifying
y = 1

 

See similar equations:

| 6x=4x-10 | | 5x+8-3x+2=20 | | 90-(12-8y)=150 | | 6x+3=-5x+14 | | 4x=-60 | | -3x=45 | | 5y=2y-42-3y | | -6+7=3(2p-3)-4(-10+4p) | | 8n+6=46 | | 37+8x=4(7-x) | | 5(2-x)=7x-26 | | 12c+15=24 | | 1.6(3y-1)+2=5y | | 2(h-8)-h=h-16 | | 8c+10=2(4c+5) | | 7x-10=6(11-2x) | | 5n-6=24 | | 3(4x-9)=5(2x-5) | | 4x+3x-9=5 | | 1.5x-1.5=0 | | 3+6z=13+6z | | 14=-8x+-10 | | 2a-2=3a+3 | | -3x-2+5x=12 | | 2x+10+3x=0 | | 2c+9=4c-9 | | 3(x-3)=5(1.5+x) | | 6(x+6)=29+7x | | 5p+6=-4-8 | | 4(a+5)=28+4a | | 8+6n=8(1+6n)+3n | | 2(x+-4)+2x=4x+-1 | | -12+3n=4n+7(n+4) | | 2(1.5m+3)=3.5m-1 | | -6v+26=4(v+7)-8v | | 33-x=-3(4x+8)-8x | | 7+5u=-43 | | -13=2b-b-10 | | -10-2a=-18 | | 8x+5-x=-2 | | -27=3(t+1) | | 3a+2(a-7)=8a-3a-14 | | 32=4x+3 | | -12=y+21 | | 4z+3=z-2 | | 5+m=13 | | -40=8+6s | | 5(3-2y)=3-4y | | 4x-6+2x=18 | | 7z+1=z-6 | | 2(x-2)-6=0 | | 4z+2=z-2 | | -16-9= | | -5(2n+4)=25 | | 3x+5=4x-2 | | 1+6(x-4)=9-2(x-2) | | (5+-6)=2(t+1)+2 | | (5t-6)=2(t+1)+2 | | x+9=-4 | | -33+23= | | -6.1r+(-4)=9.8 | | -7(t-5)-(t+4)=6 | | 3+2= | | 6(3z-1)-5(z+9)=4(z+1) | | 30=6x |